Influence of different UV spectra and intensities on yield and quality of cannabis inflorescences - Huebner, Daniel Stefan; Batarshin, Marat; Beck, Sebastian; König, Leon; Mewis, Inga; Ulrichs, Christian (Frontiers in Plant Science, 2024)
The raising economic importance of cannabis arouses interest in positively influencing the secondary plant constituents through external stimuli. One potential possibility to enhance the secondary metabolite profile is the use of UV light. In this study, the influence of spectral UV quality at different intensity levels on photomorphogenesis, growth, inflorescence yield, and secondary metabolite composition was investigated. Three UV spectra with five different intensities were considered: L1 (UVA:B = 67:33, 4.2 W/m²), L2 (UVA:B = 94:6, 4.99 W/m²), L3_1 (UVA:B = 99:1, 1.81 W/m²), L3_2 (UVA:B = 99:1, 4.12 W/m²) and L3_3 (UVA:B = 99:1, 8.36 W/m²). None of the investigated UV treatments altered the cannabinoid profile. Regarding the terpenes investigated, light variant L3_1 was able to positively influence the terpene profile. Especially linalool (+29%), limonene (+25%) and myrcene (+22%) showed an increase, compared to the control group without UV treatment. Growth and leaf morphology also showed significant changes compared to the control. While a high UVA share increased the leaf area, a higher UVB share led to a smaller leaf area. Of the UV sources examined, only L3_1 with 1.81 W/m² and a radiation dose of 117.3 kJ m² d-1 is suitable for practical use in commercial cannabis cultivation. The terpene concentration for this group was in part significantly increased with constant yield and cannabinoid concentration.